Indonesia's Free and Active Foreign Policy: ASEAN Centrality, Domestic Institutions, and the Natalegawa Doctrine Reconsidered - Sofia Trisni (JLAST : Journal of Law and Social Transformation, 2026)
This article examines the continuity and evolution of Indonesia's 'free and active' (bebas-aktif) foreign policy from its constitutional foundations to its articulation under President Susilo Bambang Yudhoyono (SBY) and Foreign Minister Marty Natalegawa. The purpose of this study is to explain the constitutional and ideological basis of Indonesia's foreign policy, the centrality of ASEAN within it, the domestic institutional factors that shape it, and how the doctrine was reinterpreted through the metaphors of "navigating a turbulent ocean" and "dynamic equilibrium." This study employs a qualitative descriptive method based on library and documentary research, drawing on primary legal and political documents as well as secondary academic literature. The findings show that Indonesia's foreign policy is anchored in the Preamble of the 1945 Constitution, that ASEAN functions as an indispensable diplomatic and security buffer, that Commission I of the House of Representatives has become an increasingly influential domestic actor since the enactment of Law No. 37/1999, and that the Yudhoyono-Natalegawa era reaffirmed rather than abandoned the bebas-aktif principle by adapting it to a more multipolar regional order. The article further situates these findings in relation to more recent scholarship to show that the doctrine has persisted, in adapted form, into the Jokowi and Prabowo presidencies. This study is limited by its reliance on documentary sources rather than primary interviews and does not provide a comprehensive comparative assessment of Indonesian foreign policy after 2014. Keywords: ASEAN centrality; bebas-aktif; foreign policy; Indonesia; Natalegawa Doctrine Abstrak Artikel ini mengkaji kesinambungan dan perkembangan politik luar negeri Indonesia yang "bebas dan aktif" (bebas-aktif), mulai dari landasan konstitusionalnya hingga artikulasinya pada masa Presiden Susilo Bambang Yudhoyono (SBY) dan Menteri Luar Negeri Marty Natalegawa. Tujuan penelitian ini adalah untuk menjelaskan dasar konstitusional dan ideologis politik luar negeri Indonesia, sentralitas ASEAN di dalamnya, faktor kelembagaan domestik yang membentuknya, serta bagaimana doktrin tersebut dimaknai ulang melalui metafora "mengarungi lautan yang bergejolak" dan "keseimbangan dinamis". Penelitian ini menggunakan metode deskriptif kualitatif berbasis studi pustaka dan dokumen, dengan memanfaatkan dokumen hukum dan politik primer serta literatur akademik sekunder. Temuan menunjukkan bahwa politik luar negeri Indonesia berakar pada Pembukaan UUD 1945, bahwa ASEAN berfungsi sebagai penyangga diplomatik dan keamanan yang tidak tergantikan, bahwa Komisi I DPR RI menjadi aktor domestik yang semakin berpengaruh sejak berlakunya UU No. 37/1999, dan bahwa era Yudhoyono-Natalegawa menegaskan kembali, bukan meninggalkan prinsip bebas-aktif dengan mengadaptasinya pada tatanan regional yang lebih multipolar. Artikel ini juga menempatkan temuan tersebut dalam kajian yang lebih baru untuk menunjukkan bahwa doktrin ini tetap bertahan, dalam bentuk yang disesuaikan, hingga era Jokowi dan Prabowo. Penelitian ini memiliki keterbatasan karena bertumpu pada sumber dokumenter dan bukan wawancara primer, serta belum memberikan penilaian komparatif yang menyeluruh atas politik luar negeri Indonesia setelah 2014. Kata kunci: bebas-aktif; Doktrin Natalegawa; Indonesia; politik luar negeri; sentralitas ASEAN